Cirrhotic Cardiomyopathy After Transplantation: Neither the Transient Nor Innocent Bystander. Issue 5 (13th October 2018) - Izzy, Manhal; Oh, Jae; Watt, Kymberly D.
Abstract : Cirrhotic cardiomyopathy in end‐stage liver disease is currently characterized by blunted contractile systolic response to stress with or without diastolic dysfunction in the absence of known heart disease. Since the establishment of the diagnostic criteria of cirrhotic cardiomyopathy in 2005, there have been multiple studies regarding its pathophysiology and pretransplant clinical course. The data regarding the post‐transplant course of this entity are sparse. This review addresses the course and prognosis of the elements of cirrhotic cardiomyopathy after liver transplantation (LT). To this end, there is limited compelling evidence demonstrating the reversibility of this entity post‐LT. Cirrhotic cardiomyopathy may, in fact, increase the risk of post‐transplant complications. This review reveals a need to refine the diagnostic criteria of cirrhotic cardiomyopathy in view of the remarkable progress in the sphere of echocardiographic evaluation of systolic and diastolic dysfunction. The post‐transplant course and outcomes related to cirrhotic cardiomyopathy may be better evaluated in the setting of updated diagnostic criteria.